2017
DOI: 10.24114/jpb.v6i2.6546
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Kesulitan Belajar Biologi Siswa Materi Bioteknologi di SMA Negeri Se-Kota Medan

Abstract: The aim of the study is to determine students’ learning difficulties at all Public Senior High School (SMA) in Medan. This research is descriptive. The population of the study is all students of class XII totaling 7272 in 21 Public Senior High Schools (SMA Negeri) spread over 15 districts. Samples were taken using Purposive Sampling, they are 524 students of class XII in 7 schools. The techniques for data collection use questionnaires of students’ learning difficulties and interviews. The finding of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
2
12
0
17
Order By: Relevance
“…The use of complex terms supported by some incomplete information in the book causes students to tend to get concepts from the internet with an unknown source that isn't known the truth of the concept. This is in line with the statement of Rahmadani et al (2017) that the use of difficult language books can lead students to cause misconceptions.…”
Section: Figure 1 Students' Misconceptions Diagram In Cellsupporting
confidence: 87%
“…The use of complex terms supported by some incomplete information in the book causes students to tend to get concepts from the internet with an unknown source that isn't known the truth of the concept. This is in line with the statement of Rahmadani et al (2017) that the use of difficult language books can lead students to cause misconceptions.…”
Section: Figure 1 Students' Misconceptions Diagram In Cellsupporting
confidence: 87%
“…Semakin rendah minat belajar peserta didik maka kesulitan belajarnya akan semakin tinggi. Hasil penelitian yang dilakukan oleh Rahmadani, W., Harahap, F., & Gultom, T (2017), menemukan bahwa kesulitan belajar peserta didik dapat dipengaruhi oleh minat, motivasi dan bakat peserta didik dengan persentase sebesar 43%.…”
Section: Pengawasan Pembelajaranunclassified
“…There are some obstacle found in cycle I, one of the problems is the motivation of the student are getting unmotivated, so the teacher need give motivation to the student first due to the learning motivation are closely related to the learning outcomes (Everaert et al, 2017;Firmansyah et al, 2018;Rahmadani et al, 2017;Wahyuni et al, 2018;Wulandari & Surjono, 2013). The result showed that mobile learning is effective to improve student learning outcomes, it is following the research results of Putra et al (2017); Fatmawati (2015); Nugroho (2014); Surahman and Surjono (2017) that the use of android application-based learning media was able to improve learning outcomes.…”
Section: Cycle IImentioning
confidence: 99%
“…The learning motivation during the pandemic also decreased (Handarini & Wulandari, 2020). There is a significant relationship between learning motivation and science learning outcomes (Everaert et al, 2017;Firmansyah et al, 2018;Rahmadani et al, 2017;Wahyuni et al, 2018;Wulandari & Surjono, 2013), and this problem must be overcome by teachers. One of the strategies to improve learning outcomes by using the Smart Apps Creator 3 application.…”
Section: Introductionmentioning
confidence: 99%